On the elasticity, adhesion, and friction of PDMS at the nanometer scale - Lee, W. J.; Ha, J. W.; Kim, J. M.; Caron, A. (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
The interdependence of adhesion, friction, and elasticity of elastomers is relevant for various engineering applications. However, its investigation has been limited to smooth glass surfaces. We apply atomic force microscopy (AFM)-based methods to quantify PDMS’s elastic and tribological properties in single asperity contacts (quasi-static and sliding) with a nanometer-scale SiOx asperity under dry conditions. The selected experimental approach allows us to model the contact initiation with PDMS and its degradation. Combining quasi-static and reciprocal sliding experiments, we identify several contributions to adhesion and friction: junction formation, elastic deformation, rupture, and adhesive material transfer. Furthermore, we find correlations between the elastic deformation of PDMS/SiO2 junctions and their adhesion hysteresis on the one hand and the shear strength and the work of adhesion on the other.